Calculation of the inner‐shell contribution to the correlation energy through DLPNO‐CEPA/1 and scaled same‐spin second‐order Møller–Plesset perturbation theory. Issue 10 (23rd January 2020) - Sánchez, Hernán R.
Abstract: The use of two low‐cost methods for the prediction of the inner‐shells contribution to the correlation energy is analyzed. The Spin‐Component‐Scaled second‐order Møller–Plesset perturbation theory (SCS‐MP2) was reparameterized for the prediction of such contributions. The best results are found when only the same spin term is considered (SSS‐MP2). The Coupled Electron Pair Approximation (CEPA) using the Domain‐based Local Pair Natural Orbital approximation (DLPNO) was also studied for the same purpose. The methods were tested for atomization energies on the W4‐11 test set using basis sets up to quadruple zeta quality. The SSS‐MP2 proved to be a marked improvement upon MP2 decreasing the root‐mean‐square‐error (RMSE) from 0.443 to 0.302 kcal mol −1 . The RMSE of DLPNO‐CEPA/1 in the test set is only 0.147 kcal mol −1 and its computational cost is very low considering the intended applications. Furthermore, a linear combination of both methods decreased the RMSE to 0.118 kcal mol −1 . Abstract : Highly accurate energy calculations require taking into account the contribution of inner‐shell electrons to the correlation energy. In this study is shown that DLPNO‐CEPA/1 and Same‐Spin‐Scaled MP2 are useful low‐cost alternatives for computing this contribution. They provide a marked improvement upon MP2.